Clinical Safety and Utility of Pediatric Balloon-assisted Enteroscopy: A Multicenter Prospective Study in Japan. Issue 3 (March 2019) - Hagiwara, Shin-ichiro; Kudo, Takahiro; Kakuta, Fumihiko; Inoue, Mikihiro; Yokoyama, Koji; Umetsu, Shuichiro; Iwama, Itaru; Yodoshi, Toshifumi; Tatsuki, Maiko; Shimizu, Toshiaki; Nakayama, Yoshiko
ABSTRACT: Objectives: The benefit of balloon-assisted enteroscopy (BAE) had been recently documented in pediatric patients, but previous reports are based on single institution experiences. We evaluated the feasibility of pediatric BAE in 8 tertiary referral hospitals throughout Japan. Methods: This was a prospective, multi-institutional study. Patients younger than 18 years were enrolled between April 2014 and March 2017 to undergo double-balloon or single-balloon enteroscopy. Data were collected prospectively using a standardized questionnaire. Results: We enrolled 79 pediatric patients (96 procedures, 70 boys, 26 girls; median age 12.7 years, range 1–17 years). Antegrade (oral-route) BAE was performed in 20 procedures (lowest body weight 12.9 kg, youngest age 3.7 years), and retrograde (anal-route) BAE in 76 (lowest body weight 10.8 kg, youngest age 1.6 years). Severe adverse events were associated with BAE in 2 patients: 1 with hemorrhage due to polypectomy and 1 with pancreatitis after double-balloon endoscopic retrograde cholangioscopy. No intestinal perforation was reported. Procedure duration of oral-route BAE for diagnosis was significantly longer than anal-route for diagnosis ( P  < 0.001). The overall diagnostic yield for rectal bleeding/positive fecal occult blood test and abdominal pain was 48%. Among 40 patients referred for diagnosis who did not undergo capsule endoscopy, diagnoses were confirmed in 17 (42.5%) patients after BAE. Conclusions: This prospective multicenter observational study documents the efficacy of BAE in pediatric patients. Abstract : Supplemental Digital Content is available in the text